2018
DOI: 10.1080/10717544.2018.1450909
|View full text |Cite
|
Sign up to set email alerts
|

Nasal delivery of H5N1 avian influenza vaccine formulated with GenJet™ or in vivo-jetPEI®induces enhanced serological, cellular and protective immune responses

Abstract: Avian influenza virus infection is a serious public health threat and preventive vaccination is the most cost-effective public health intervention strategy. Unfortunately, currently available unadjuvanted avian influenza vaccines are poorly immunogenic and alternative vaccine formulations and delivery strategies are in urgent need to reduce the high risk of avian influenza pandemics. Cationic polymers have been widely used as vectors for gene delivery in vitro and in vivo. In this study, we formulated H5N1 inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…These intricate interactions during vaccination process might explain why the DDP regimen led to the induction of higher level of antibody and cytokine responses and conferred more effective protection against DENV2 than the DDD or DPP. Taken together, the results suggested that the heterologous DDP immunization regimen would be advantageous in significantly improving the DENV2-specific CD8 + responses and simultaneous Th1 and Th2 responses (Aviles et al, 2015; Wang et al, 2017; Cao et al, 2018; Jung et al, 2018). Therefore, the DDP vaccination regimen would be an appropriate strategy for developing dengue vaccines.…”
Section: Discussionmentioning
confidence: 78%
“…These intricate interactions during vaccination process might explain why the DDP regimen led to the induction of higher level of antibody and cytokine responses and conferred more effective protection against DENV2 than the DDD or DPP. Taken together, the results suggested that the heterologous DDP immunization regimen would be advantageous in significantly improving the DENV2-specific CD8 + responses and simultaneous Th1 and Th2 responses (Aviles et al, 2015; Wang et al, 2017; Cao et al, 2018; Jung et al, 2018). Therefore, the DDP vaccination regimen would be an appropriate strategy for developing dengue vaccines.…”
Section: Discussionmentioning
confidence: 78%
“…This was not limited to H1N1 but was also used for H3N2 vaccine . The delivery of H5N1 vaccines with cationic polymer such as jetPEI enhanced the immunogenicity and induced antigen specific CD4, CD8 and B cell responses . Polyamidoamine (PAMAM) dendrimers conjugated with 3′- and 6′-sillylactose (3SL and 6SL) were designed and underwent a hemagglutination inhibition assay (HIA, Figure ) with human and avian viruses.…”
Section: Specific Diseasesmentioning
confidence: 99%
“…83 The delivery of H5N1 vaccines with cationic polymer such as jetPEI enhanced the immunogenicity and induced antigen specific CD4, CD8 and B cell responses. 84 Polyamidoamine (PAMAM) dendrimers conjugated with 3′and 6′-sillylactose (3SL and 6SL) were designed and underwent a hemagglutination inhibition assay (HIA, Figure 6) with human and avian viruses. HIA results show that dendrimers conjugated with 6SL inhibit human avian influenza better than those conjugated with 3SL.…”
Section: Flu (Influenza)mentioning
confidence: 99%
“…Since first reported in 1995, PEI has been becoming one of the most widely studied gene vehicles characterized with high positive charge density and ‘proton sponge effect’, by which genes can be robustly condensed and protected from endosome or lysozyme capture (Boussif et al., 1995 ; Regnström et al., 2003 ). Transfection reagents such as Gen500, jetPEI, which is developed based on HMW PEIs, are commercially available (Li et al., 2015 ; Cao et al., 2018 ). However, high-gene transfection efficiency always comes along with high cytotoxicity by HMW PEIs (Chollet et al., 2002 ).…”
Section: Introductionmentioning
confidence: 99%